МИЙНЕТ РЕСУРСЛАРЫНЫҢ ҚӘЛИПЛЕСИЎИНДЕ ДЕМОГРАФИЯЛЫҚ ТИЙКАРЛАР - Утепова, Г.Б. (FAN va JAMIYAT, 2020)
The reviewed article are studied the most important socio-economic problems of the demographic and methodological basis for the movement and labor resources of the population.